2022
DOI: 10.1111/resp.14431
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the clinical utility of sGaw as a response variable in methacholine challenge testing

Abstract: Background and Objective Airway hyperresponsiveness (AHR) is commonly assessed by a methacholine challenge test (MCT), during which a provocative concentration causing a 20% reduction in forced expiratory volume in 1 second (FEV1) (PC20) < 8 mg/ml is considered a positive response. However, a fall in specific airway conductance (sGaw) may also have clinical significance. The purpose of this study was to assess whether AHR determined by a provocative concentration causing a 40% reduction in sGaw (PC40) < 8 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Существует прямая связь между гиперреактивностью дыхательных путей, функцией легких и антропометрическими параметрами человека, а следовательно, размерами дыхательных путей. Так, на метахолин чаще реагируют женщины вследствие более высокой, по сравнению с мужчинами, восприимчивости к различным раздражающим агентам и меньшего размера дыхательных путей [4]. В то же время гиперреактивность дыхательных путей более распространена у мальчиков до начала полового созревания [5].…”
Section: распространенность гиперреактивности дыхательных путейunclassified
“…Существует прямая связь между гиперреактивностью дыхательных путей, функцией легких и антропометрическими параметрами человека, а следовательно, размерами дыхательных путей. Так, на метахолин чаще реагируют женщины вследствие более высокой, по сравнению с мужчинами, восприимчивости к различным раздражающим агентам и меньшего размера дыхательных путей [4]. В то же время гиперреактивность дыхательных путей более распространена у мальчиков до начала полового созревания [5].…”
Section: распространенность гиперреактивности дыхательных путейunclassified
“…What should be regarded as a positive change has been subject to debate, 7 and due to its inherent variability, a larger percent change in sGaw than FEV 1 is required for a positive test. In this Respirology article, 2 the authors found a PC40 to be highly sensitive for a subsequent asthma diagnosis (93%); however, physicians were not blinded to the outcome of the challenge test and so the high sensitivity of the PC40 should be interpreted in this context. It is possible (and relevant) that this high specificity is an indication that the PC40 was incorporated into the physician's diagnosis.…”
mentioning
confidence: 95%
“…Finally, like oscillometry, sGaw should not, and indeed cannot, be used as a surrogate for spirometry as the association between FEV 1 and sGaw is weak at best (fig. 8 of Reference 2). This discrepancy likely reflects that FEV 1 and sGaw describe related but distinct physiological changes in the airways, and the article by Parker et al provides evidence that both outcomes (FEV 1 and sGaw) are of probable clinical relevance.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In the May issue of Respirology, Parker et al reported the findings of their study of the utility of specific airway conductance (sGaw) as a response variable in direct bronchoprovocation tests using methacholine. 6 They reviewed the results of 211 challenge tests from a random selection of 300, with 89 excluded due to missing data. Their cohort had a mean age of 53 years, 67% were female, the median BMI was 29 kg/m 2 , and 38% were current or former smokers.…”
mentioning
confidence: 99%